1997
DOI: 10.1097/00002820-199710000-00005
|View full text |Cite
|
Sign up to set email alerts
|

Relaxation to reduce nausea, vomiting, and anxiety induced by chemotherapy in Japanese patients

Abstract: The purpose of this study was to examine the effectiveness of progressive muscle relaxation (PMR) in reducing the nausea, vomiting, and anxiety induced by chemotherapy in Japanese patients. Subjects comprised 60 cancer chemotherapy patients who were hospitalized in a cancer center. These subjects were randomly assigned to either the experimental or control group. In addition to routine nursing care, subjects in the experimental received PMR training, while those in the control received contact with the investi… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
74
0
3

Year Published

2002
2002
2018
2018

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 90 publications
(80 citation statements)
references
References 13 publications
3
74
0
3
Order By: Relevance
“…Studies carried out in different fields (stoma patients, patients receiving chemotherapy, dialysis and psychiatric patients, etc) have proved progressive relaxation exercises to be effective in reducing anxiety (9,(16)(17)(18)(19)(20)(21)(38)(39)(40)(41)(42)(43). Dehdari et al (44) applied to patients after CABG surgery studies of state and permanent PMR by reducing levels of anxiety reported that improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Studies carried out in different fields (stoma patients, patients receiving chemotherapy, dialysis and psychiatric patients, etc) have proved progressive relaxation exercises to be effective in reducing anxiety (9,(16)(17)(18)(19)(20)(21)(38)(39)(40)(41)(42)(43). Dehdari et al (44) applied to patients after CABG surgery studies of state and permanent PMR by reducing levels of anxiety reported that improve the quality of life.…”
Section: Discussionmentioning
confidence: 99%
“…From this research until today, it was found that nursing researcher used PMR in some chronic disease processes, preventing side effects of chemotherapy and dialysis, decrease the pain of patients on surgery and reduce the anxiety level of psychiatry patients, cardiac rehabilitation patients and university students (9)(10)(11)(12)(13)(14)(15)(16)(17)(18)(19)(20)(21).…”
Section: Introductionmentioning
confidence: 99%
“…Clients with generalized anxiety disorder frequently show symptoms of depression Chambless and Gillis (1996, p.122) compared three studies of different researchers and found CBT to have greater impact on depression than behavior therapy (Butler et al, 1991); CBT was superior to nondirective therapy but not to applied relaxation (Borkovec &Costello, 1993); further Borkovec et al(1987) showed that there were no significantly superior CBT effects for depression among treatment completers. Further more Arakawa (1997) showed the efficacy of progressive muscle relaxation to reduce nausea, vomiting and anxiety induced by chemotherapy. Somewhat recently Hoyer et al (2009) investigated the efficacy of worry exposure and applied relaxation therapeutic techniques for the treatment of generalized anxiety disorder, while comparing with control group both were found to be effective.…”
Section: Introductionmentioning
confidence: 99%
“…Luebbert, Dahme ve Hasenbring'in [39] yaptığı meta analiz sonuçlarına göre bulantı ve diğer semptomlar gevşeme yöntemi ile önemli ve tutarlı bir şekil-de azalmaktadır. Arakawa'nın [40] 60 Japon hasta ile yapmış olduğu çalışmada da progresif kas gevşe-me egzersizi ile kemoterapiye bağlı gecikmiş bulantı ve kusma sıklığında azalma olmuştur.…”
Section: Bitkisel Tedavilerunclassified